ANALISA RASIO LAPORAN KEUANGAN UNTUK MENILAI KINERJA PERUSAHAAN PT ASTRA AGRO LESTARI TBK - Denny Erica (MONETER - JURNAL AKUNTANSI DAN KEUANGAN, 2016)
As one of the largest oil palm plantation in Indonesia, which has been operating from the date of October 3, 1988, PT Astra Agro Lestari Tbk (Persero), will have financial statements that must always be analyzed sequentially from one period to the next to be used as the basis of the information can be useful either by internal or external parties of the company, and in this case the company may use a ratio analysis of financial statements. as the data collection methods used in this study can be used method of observation and study of literature related to financial data company, to then be analyzed by calculating the ratio of arithmetic can be interpreted in economic relations associated with the performance of the company. The results of the analysis of financial statements with the measurement of Liquidity Ratio, Leverage Ratio, Activity Ratio, Profitability Ratio, it can be said the company in a state quite well. Keywords : The company's performance, financial statement ratio analysis.